Mehmet Rauf’s Novel September: One of the first novels written under the influence of Western literature and its critical analysis - Sultanishvili Gezgic, Shorena (European Scientific Journal, ESJ, 2025)
The scientific article aims to analyze the factors provoking betrayal and the origin of remorse and to present psychological portraits of the characters in Mehmed Rauf’s acclaimed novel "September", which is considered the first psychological novel in Turkish literature of the Serveti-i-Funun period. The article applies the method of content analysis and critical study of the scientific literature related to the novel itself and the analysis of new tendencies in Turkish literature. Based directly on the novel’s text, the article studies the reasons and the source of betrayal, its impact on the characters, and the tormenting feelings caused by remorse. New psychological motives that appear in the novel "September" could be considered as an original phenomenon in Turkish literature in the period around 1900; Though the end of the novel is tragic, the characters of “September” are forgiven for their “misdeeds” as the death of the main heroes purifies their sins.